Graphene-based nanomaterials for peripheral nerve regeneration - Convertino, Domenica; Trincavelli, Maria Letizia; Giacomelli, Chiara; Marchetti, Laura; Coletti, Camilla (Frontiers in Bioengineering and Biotechnology, 2023)
Emerging nanotechnologies offer numerous opportunities in the field of regenerative medicine and have been widely explored to design novel scaffolds for the regeneration and stimulation of nerve tissue. In this review, we focus on peripheral nerve regeneration. First, we introduce the biomedical problem and the present status of nerve conduits that can be used to guide, fasten and enhance regeneration. Then, we thoroughly discuss graphene as an emerging candidate in nerve tissue engineering, in light of its chemical, tribological and electrical properties. We introduce the graphene forms commonly used as neural interfaces, briefly review their applications, and discuss their potential toxicity. We then focus on the adoption of graphene in peripheral nervous system applications, a research field that has gained in the last years ever-increasing attention. We discuss the potential integration of graphene in guidance conduits, and critically review graphene interaction not only with peripheral neurons, but also with non-neural cells involved in nerve regeneration; indeed, the latter have recently emerged as central players in modulating the immune and inflammatory response and accelerating the growth of new tissue.